Impact of intravenous and topical lidocaine on clinical outcomes in patients receiving propofol for gastrointestinal endoscopic procedures: a meta-analysis of randomised controlled trials. (April 2022) - Hung, Kuo-Chuan; Yew, Ming; Lin, Yao-Tsung; Chen, Jen-Yin; Wang, Li-Kai; Chang, Ying-Jen; Chang, Yang-Pei; Lan, Kuo-Mao; Ho, Chun-Ning; Sun, Cheuk-Kwan
Abstract: Background: The efficacy of i.v. or topical lidocaine as an anaesthesia adjunct in improving clinical outcomes in patients receiving gastrointestinal endoscopic procedures under propofol sedation remains unclear. Methods: Electronic databases (MEDLINE, EMBASE, and Cochrane Library) were searched for RCTs comparing the clinical outcomes with or without lidocaine application (i.v. or topical) in patients receiving propofol for gastrointestinal endoscopic procedures from inception to 29 March 2021. The primary outcome was propofol dosage, while secondary outcomes included procedure time, recovery time, adverse events (e.g. oxygen desaturation), post-procedural pain, and levels of endoscopist and patient satisfaction. Results: Twelve trials (1707 patients) published between 2011 and 2020 demonstrated that addition of i.v. ( n =7) or topical ( n =5) lidocaine to propofol sedation decreased the level of post-procedural pain (standardised mean difference [SMD]=-0.47, 95% confidence interval [CI]: -0.8 to -0.14), risks of gag events (risk ratio [RR]=0.51, 95% CI: 0.35–0.75), and involuntary movement (RR=0.4, 95% CI: 0.16–0.96). Subgroup analysis demonstrated that only i.v. lidocaine reduced propofol dosage required for gastrointestinal endoscopic procedures (SMD=-0.83, 95% CI: -1.19 to -0.47), increased endoscopist satisfaction (SMD=0.75, 95% CI: 0.21–1.29), and shortened the recovery time (SMD=-0.83, 95% CI: -1.45 to -0.21). Intravenous or topical lidocaine did not affect the incidence of oxygen desaturation (RR=0.72, 95% CI: 0.41–1.24) or arterial hypotension (RR=0.6, 95% CI: 0.22–1.65) and procedure time (SMD=0.21, 95% CI: -0.09 to 0.51). Conclusion: This meta-analysis demonstrated that i.v. or topical lidocaine appears safe to use and may be of benefit for improving propofol sedation in patients undergoing gastrointestinal endoscopic procedures. Further large-scale trials are warranted to support our findings.